Prevalence of type 2 diabetes mellitus in a representative sample of Greek adults and its association with modifiable risk factors: results from the Hellenic National Nutrition and Health Survey. (August 2021) - Magriplis, E.; Panagiotakos, D.; Papakonstantinou, E.; Mitsopoulou, A.-V.; Karageorgou, D.; Dimakopoulos, I.; Bakogianni, I.; Chourdakis, M.; Micha, R.; Michas, G.; Ntouroupi, T.; Tsaniklidou, S.-M.; et al.
Abstract: Objective: Diabetes mellitus is a disease associated with many complications leading to premature death. The aim of this study was to estimate prevalence of type 2 diabetes (T2D), and the proportion of the population unaware of the condition, in association with modifiable risk factors. Study design: Data from the Hellenic National Nutrition and Health Survey were used ( n  = 3773 adults, 40.8% men) and were obtained by trained personnel. Methods: Diabetes mellitus disease status was categorized as per the International Classification of Diseases codes (10th version). A subsample from the two main metropolitan areas was used to assess T2D and impaired fasting glucose (IFG) ( n  = 990; 38.2% men) from plasma analysis. Results: The prevalence of T2D in the population was 5.2% in total, reaching 13.7% in adults aged >60 years (no sex differences). IFG was observed in 27.3% of adults in the two metropolitan areas, and 40% were unaware of having T2D in this subsample. The likelihood of having T2D significantly increased with age and body weight, whereas it decreased with higher educational level and physical activity (P for all <0.001). Conclusion: The high T2D prevalence in adults, especially among the older age-groups, suggests a major public health problem in Greece. Highlights: Impaired fasting glucose was observed in 27.3% of adults in the two metropolitan areas, and 40% were unaware of having T2D. Odds of T2D significantly increased with age and body weight, and decreased with educational level and physical activity. The population prevalence of T2D was found 5.2% in total, reaching 13.7% in adults aged >60 years (no sex differences).